Comparative analysis of KNOX genes and their expression patterns under various treatments in Dendrobium huoshanense - Li, Guohui; Manzoor, Muhammad Aamir; Wang, Guoyu; Chen, Cunwu; Song, Cheng (Frontiers in Plant Science, 2023)
KNOX plays a pivotal role in governing plant growth, development, and their responses to diverse abiotic and biotic stresses. However, information on the relationship between the KNOX gene family and expression levels under different treatments in Dendrobium is still limited. To address this problem, we first use bioinformatics methods, and revealed the presence of 19 KNOX genes distributed among 13 chromosomes in the D. huoshanense genome. Through an analysis of phylogenetic relationships, these genes classified into three distinct clades: Class I, Class II, and Class M. Our investigation included promoter analysis, revealing various cis-acting elements associated with hormones, growth and development, and abiotic stress responses. Additionally, qRT-PCR experiments were conducted to assess the expression patterns of DhKNOX genes under different treatments, including ABA, MeJA, SA, and drought. The results demonstrated differential expression of DhKNOX genes in response to these treatments, thereby highlighting their potential roles in stress adaptation. Overall, our results contribute important insights for further investigations into the functional characterization of the Dendrobium KNOX gene family, shedding light on their roles in plant development and stress responses.